The influence of empowering team leadership on employees' innovation passion in high-tech enterprises - Jing, Jing; Wang, Shujun; Yang, Jiaoping; Ding, Tianwei (Frontiers in Psychology, 2022)
How to stimulate the innovation passion of employees and then improve the innovation performance of enterprises is an important proposition faced by high-tech enterprises. Whether and how to stimulate the innovation passion of employees is of great research value. Based on the social information processing theory, this paper takes innovation self-efficiency and innovation climate based on advantages as the path variable, and obtains the following conclusions through cross-level analysis with the data of 93 high-tech enterprises as the sample: The empowering team leadership has cross-level direct positive influence and indirect positive influence on innovation passion, and the innovation self-efficiency and innovation climate based on advantages positively adjust the relationship between innovation self-efficiency and innovation passion. At the same time, innovation climate based on advantages positively moderates the relationship between innovation self-efficacy and innovation passion. This paper has some innovations in exploring the function mechanism of empowering team leadership on employees' innovation passion, and the relevant conclusions can guide the innovation management of high-tech enterprises.